Exploring coaching and follow-up supports in community-implemented caregiver-mediated JASPER intervention. (April 2022) - Shire, Stephanie Y; Shih, Wendy; Barriault, Terri; Kasari, Connie
Although a growing number of caregiver-mediated intervention models for families with children with autism are being examined in efficacy trials, few have been transferred to community implementation. Furthermore, little testing has explored implementation strategies to support caregivers' strategy use with their children. In partnership with a publicly funded intervention agency in Canada, this pilot project explored intervention implementation strategies and follow-up supports. Dyads were randomized at entry to coaching or observe then add coaching and at intervention exit to individual or group follow-up booster. The caregiver-mediated Joint Attention, Symbolic Play, Engagement and Regulation intervention was provided by agency staff to a diverse community sample of families with young children awaiting or diagnosed with autism spectrum disorder. Independent agency staff delivered assessments and recorded a caregiver–child interaction. Blinded raters scored children's initiations of joint attention, play actions, joint engagement, and caregivers' strategy implementation. Practitioners implemented the intervention and coaching strategies well ( M = 83%). Overall, caregivers made significant gains in strategy use and children showed significant growth in joint engagement, play diversity, and joint attention across conditions through public caregiver-mediated intervention services. Caregivers' strategy use supported gains in children's joint engagement. Lay abstract: The next step for communication interventions for young children with autism include coaching/teaching for caregivers that have been tested in university clinics and testing these interventions in real world systems with early intervention providers who serve children and families in their communities. However, there are few projects that have tested how well the intervention can be transferred to community providers and what types of progress children and caregivers make in these services. This project took place in partnership with a community early intervention agency in the province of Ontario, Canada. The agency provided government-funded public health services. The agency was funded to take part in a pilot program to try out one of four early intervention models that included coaching for caregivers and was designed to support children's social engagement, play, and communication skills. The team decided to test two ways to start the intervention: (a) begin with observation of the practitioner for 4 weeks and then start coached practice with the child and (b) start coaching immediately. The team also tested two ways to support families for 3 months after intervention: (a) group booster sessions and (b) individual visits. The practitioners delivered the intervention well ( M = 83%), and overall, caregivers and children made significant gains by the end of intervention in both observation + coaching and coaching. Attendance for follow-up boosters was variable with fewer families attending groups. More research is needed to test different strategies and roles to individualize interventions for caregivers with a range of goals and learning styles.